2015
DOI: 10.2527/jas.2015-9391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immunological challenge induced by lipopolysaccharide on skeletal muscle fiber type conversion of piglets1

Abstract: The objective of this study was to investigate the effects of immunological challenge on the skeletal muscle fiber type conversion of piglets. Sixteen Large White weaned barrows (28 ± 3 d, 8.22 ± 0.89 kg BW) were allotted by weight and litter to 2 groups: the control group and the lipopolysaccharide (LPS) group. Saline (control) or LPS was injected intravenously via a jugular catheter on d 1, 3, 5, 7, 9, 11, 13, and 15 at an initial dosage of 80 μg/kg BW, which was increased by 30% at each subsequent injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…In our previous study, LPS challenged piglets were found with increased plasma pro‐inflammatory cytokines (IL‐6 and IL‐1β) concentration ( P <0.05) on day 1, 5 and 9. But on day 13, no significant difference in concentration of pro‐inflammatory cytokines was observed between control and LPS treatment group samples . However, to our surprise, our SWATH analysis showed that even on day 15, there is a significant difference in abundance of differentially expressed proteins that were closely related to the expression of common inflammatory mediators, such as IL‐6, IL‐1β and TNF‐α (detailed in Table ).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In our previous study, LPS challenged piglets were found with increased plasma pro‐inflammatory cytokines (IL‐6 and IL‐1β) concentration ( P <0.05) on day 1, 5 and 9. But on day 13, no significant difference in concentration of pro‐inflammatory cytokines was observed between control and LPS treatment group samples . However, to our surprise, our SWATH analysis showed that even on day 15, there is a significant difference in abundance of differentially expressed proteins that were closely related to the expression of common inflammatory mediators, such as IL‐6, IL‐1β and TNF‐α (detailed in Table ).…”
Section: Discussionmentioning
confidence: 74%
“…Our laboratory has a long‐standing research interest in understanding molecular mechanisms of LPS‐induced immunological stress using weaned piglets as a model. Previously we have examined LPS‐induced inflammation along with the high levels of plasma IL‐1β, IL‐6 and TNF‐α in the initial stages of the experiment . However, the levels of inflammatory cytokines to LPS challenge were attenuated during subsequent injections after 13 days .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we elucidated that first effect of lower cholesterol content in the hypothalamus was related to the lower body weight, which was in agreement with recent finding that an increase level of methyl donor during prenatal stage significantly downregulated the body weight of offspring in female rat ( Giudicelli et al., 2013 ). Other studies documented that methyl donor supplementation increased of fetus weight in rat ( Oster et al., 2016 ) and birth weight in swine ( Jia et al., 2015 ), because low maternal methyl donor associated with the decreased birth weight. Negative transgenerational effects about glucose metabolism in F1 and F2 offspring were reported in reduction of protein's diet model ( Pinheiro et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%